La asociación de México con el Mercosur como paso fundamental para la unidad de las Américas - Hakim, Miguel (Revista Mexicana de Política Exterior, 2022)
In this essay, the author makes a broad analysis of current conditions in Latin America and the Caribbean (LAC) and the historic characteristics of the region as a lead-up to an overview of the process of Latin American unity and some of the mechanisms that have been implemented to promote integration. Mexico, he says, perceives integration in Latin America and the Caribbean as a decision of high strategic value, fundamental to its own foreign policy. Mexico’s request to join Mercosur was presented by President Vicente Fox Quesada in July, 2004, and the country will be formally admitted as an Associated State once a free trade agreement has been signed by the parties. Hakim goes on to highlight the importance of Mexico as a means of channeling resources between the north and south of the continent, and the latest political contacts in the country’s relations with Argentina, Brazil, Paraguay and Uruguay. Finally, the author makes several comments on the prospects and opportunities that incorporation into this regional bloc will entail for Mexico.